ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN NILAI KAPITALISASI PASAR TERHADAP RETURN SAHAM - syah, Ardian; Mardiati, Endang (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this research is to examine the influence of fundamental factors which represented by the variable earnings per share (EPS), return on assets (ROA), leverage ratio (LEV), price earnings ratio (PER), return on equity (ROE), and price book value (PBV) by considering the market capitalization (MarCap) to stock returns of listed companies who belonging to the LQ45 index in Indonesia Stock Exchange. The samples of this research are 31 companies that consistently incorporated in the LQ45 index during 2009-2011 by using purposive sampling. The data used are the financial statements and financial ratios of each sample companies, which is published through the website www.idx.co.id. The analysis technique used in this study is multiple regression. Hypothesis testing using t statistics to test the effect of partial variables and F test statistics for testing simultaneous variables on stock returns with a significance level of 5%. The results showed that the fundamental factors which represented by EPS, ROA, LEV, PER, ROE, PBV and market capitalization simultaneously influence to the stock return of listed companies who belonging to the LQ45 index in Indonesia Stock Exchange. The fundamentals factor which has partial influence on stock returns is LEV and PER. The results of this research indicate that the fundamental factors which are measured by the leverage ratio (LEV) and price earnings ratio (PER) can be used by investors to predict the stock returns of listed companies who belonging to the LQ45 index in the period 2009-2011. Keyword: Stock Return, EPS, ROA, LEV, PER, ROE, PBV, MarCap.